1990
DOI: 10.1177/0164027590122004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Elderly Nursing Home Admissions

Abstract: Predictors of elderly nursing home admissions were identified using the 1982-1984 National Long-Term Care Survey. The authors found age and health factors were important predictors. Gender was not a significant predictor for disabled elderly admissions when controlling for other variables, even though women constitute the vast majority of nursing home residents. Three of four measures of informal support availability and use were not significantly related to nursing home admission by the disabled. Income and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These findings showed that older adults' personal factors predicting older adults' residential transitions are differ-ent from the factors predicting nursing home use. The literature has reported having more informal support to be both associated with and not associated with increased risk of nursing home admission [1,18,31]. Our study findings provided further explanation: that lack of informal support could predict older adults' nursinghome admission, but not older adults' residential transitions.…”
Section: Older Adults' Personal Factors and Their Residential Transitsupporting
confidence: 57%
See 1 more Smart Citation
“…These findings showed that older adults' personal factors predicting older adults' residential transitions are differ-ent from the factors predicting nursing home use. The literature has reported having more informal support to be both associated with and not associated with increased risk of nursing home admission [1,18,31]. Our study findings provided further explanation: that lack of informal support could predict older adults' nursinghome admission, but not older adults' residential transitions.…”
Section: Older Adults' Personal Factors and Their Residential Transitsupporting
confidence: 57%
“…Factors that predict older adults' nursing home use have been investigated for decades [1,2]. Many personal factors, such as age, education level, and social support, have been found to be significantly predict older adults' subsequent nursing home use [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, prior use of the service being examined is highly predictive of the likelihood of future use (Hanley, et al, 1990;Parboosingh & Larsen, 1987). For instance, those having prior hospital admissions were twice as likely to be subsequently admitted than those without prior admissions, while those with prior nursing home admissions were three and three-quarters times more likely to be subsequently admitted than those without prior admissions.…”
Section: Resultsmentioning
confidence: 53%
“…Specifically, at age 85 and above, prevalence among white females was 259/1,000 compared to 163/ 1,000 for black females, 151/1,000 for white males, and 96/1,000 for black males of the same age. Methods used to model incident risk of nursing home use range from retrospective, based on the characteristics of persons already residing in nursing homes (38), to prospective studies of variable duration (39)(40)(41).…”
Section: Relationship Between Musculoskeletal Disease and Predictors mentioning
confidence: 99%